Pengaruh Penerapan Sanksi Terhadap Pengembalian Kredit Macet Pada Lembaga Keuangan Mikro Agribisnis (LKMA) Di Kabupaten Pesisir Selatan - Melta Dwi Jayanti; Endrizal Ridwan; Hefrizal Handra (Universitas Medan Area, 2022)
Micro credit is a loan that is intended for the poor to continue their business. Since 2008, the Government has distributed micro credit assistance through the Rural Agribusiness DevelopmentProgram (PUAP) which is managed by the Agribusiness Microfinance Institution (LKMA). In theimplementation of this credit, there are still many bad loans. This study aims to determine the effectof the application of sanctions on the repayment of bad credit at the Agribusiness MicrofinanceInstitution (LKMA) in Pesisir Selatan Regency. The object of this research is the LKMA in PesisirSelatan Regency which was founded in 2011 - 2015 as many as 70 LKMA. Evaluation of the effect ofsanctions on LKMA credit returns is carried out using the Propensity Score Matching (PSM) methodbased on factors that significantly influence the LKMA's decision to apply sanctions. The factors thatsignificantly influence LKMA decisions are obtained from the results of logistic regression.Furthermore, the matching is done using the Nearest Neighbor Matching (NNM) method. Outcomethat is compared is the amount of arrears and length of arrears of credit. The results show thatsanctions have a positive effect on LKMA credit repayments as seen from the side of the length ofarrears because the longer the farmers are in arrears, the greater the sanctions imposed, so thatfarmers will seek to repay credit in a faster time. Meanwhile, in terms of the amount of arrears,sanctions do not have a significant effect on the repayment of bad debts